TINJAUAN HUKUM TERHADAP EKSONERASI PERJANJIAN INVESTASI ANTARA NASABAH DENGAN PERUSAHAAN PIALANG BERJANGKA PT RIFAN FINANCINDO BERJANGKA PEKANBARU - Zaswari '; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Brokerage is a business entity that carries out the activities as intermediary for the sale and sale of futures and on the command / message of a third party (the customer) and the right to a deposit (margin) for each of these transactions in Compliance with the regulations. The interest in protecting their clients, futures brokers, must know the state of the ability of its clients, both in terms of financing (financial), customer knowledge on trade in futures and also ensuring its customers no Action contrary to regulation.The problem in this document is the exemption from the investment agreement between the customer and the company Broker and legal protection for clients who get injured from IBs called in this case the Broker Broker Penganturan is not independent of the Law No. 10 Year 2011 regarding Commodity Futures Trading as well as Act No. 32 of 1997 on Commodity Futures Trading.Normative study of the research is to compare the principles of the agreement, can be seen a few things. First of all, the agreement that is in the Broker's violation and in violation of the 2011 Law No 11 of the Futures Trading Komooditi contained elements of an exemption clause defined as liberating your responsibilities as a result of legal effects that occur Due to the lack of performance of liability obligations required by law. Secondly, the legal protection of the Customer who gets hurt promises a broker broker and as well as the realization of the compensation fund must be given to the customer who is injured on that promise within the meaning of article 1, paragraph 23 of the law no 10 of 2011 regarding Futures Trading merchandise.Keywords: Brokerage, Exemption Treaty, Principles of Treaty and Legal Protection.